Frasa Nomina pada Berita tentang Universitas Negeri Semarang dalam Laman Suara Merdeka Edisi Agustus 2025 - Alfi Ashila; Mohammad Sofwan Azizi; Sevia Amartha Putri; Nazwa Cahya Ardiyani; Syafa Rahmadani; Didi Pramono; Lailia Ummi Rosyidah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study is motivated by the importance of understanding syntactic structures in Indonesian, particularly noun phrases that are frequently used in news texts. Noun phrases play a crucial role in ensuring clarity of meaning and accuracy of information, especially in journalistic language that emphasizes conciseness and precision. The aim of this research is to identify the types and analyze the structural patterns of noun phrases found in news articles about Universitas Negeri Semarang on the Suara Merdeka online portal, August 2025 edition. This research employs a qualitative descriptive method with data collected through the observation and note-taking technique, followed by distributional analysis to classify phrase types and structures. The results reveal three main types of noun phrases: modificative, coordinative, and appositive, with the Diterangkan–Menerangkan (DM) pattern being the most dominant. This dominance indicates the journalistic tendency toward concise and efficient expression. The findings contribute theoretically to linguistic studies, particularly syntax, and practically offer helpful sugestions for journalists, educators, and students to improve accuracy and effectiveness in academic and journalistic writing.